Venous thromboembolism, interleukin-6 and survival outcomes in patients with advanced ovarian clear cell carcinoma. Issue 14 (September 2015) - Matsuo, Koji; Hasegawa, Kosei; Yoshino, Kiyoshi; Murakami, Ryusuke; Hisamatsu, Takeshi; Stone, Rebecca L.; Previs, Rebecca A.; Hansen, Jean M.; Ikeda, Yuji; Miyara, Akiko; Hiramatsu, Kosuke; Enomoto, Takayuki; et al.
Abstract Background We compared survival outcomes and risk of venous thromboembolism (VTE) among patients with advanced and early-stage ovarian clear cell carcinoma (OCCC) and serous ovarian carcinoma (SOC), as well as potential links with interleukin-6 (IL-6) levels. Methods A multicenter case-control study was conducted in 370 patients with OCCC and 938 with SOC. In a subset of 200 cases, pretreatment plasma IL-6 levels were examined. Findings Patients with advanced OCCC had the highest 2-year cumulative VTE rates (advanced OCCC 43.1%, advanced SOC 16.2%, early-stage OCCC 11.9% and early-stage SOC 6.4%, P < 0.0001) and the highest median levels of IL-6 (advanced OCCC 17.8 pg/mL, advanced SOC 9.0 pg/mL, early-stage OCCC 4.2 pg/mL and early-stage SOC 5.0 pg/mL, P = 0.006). Advanced OCCC (hazard ratio [HR] 3.38, P < 0.0001), thrombocytosis (HR 1.42, P = 0.032) and elevated IL-6 (HR 8.90, P = 0.046) were independent predictors of VTE. In multivariate analysis, patients with advanced OCCC had significantly poorer 5-year progression-free and overall survival rates than those with advanced SOC (P < 0.01), and thrombocytosis was an independent predictor of decreased survival outcomes (P < 0.01). Elevated IL-6 levels led to poorer 2-year progression-free survival rates in patients with OCCC (50% versus 87.5%, HR 4.89, P = 0.016) than in those with SOC (24.9% versus 40.8%, HR 1.40, P = 0.07). Interpretation Advanced OCCC is associated with an increased incidence of VTE and decreased survival outcomes, which has major implications for clinical management of OCCC.